Desenvolvimento e caracterização de micro/nanossuspensões com propriedades mucoadesivas para liberação cólon-específica de metotrexato - Santos, Aline Martins dos [UNESP] (2015)
The methotrexate (MTX) is pH-dependent solubility drug used in the treatment of gastrintestinal diseases, such as Crohn's disease, ulcerative colitis and colorectal carcinomas. The micro/nanosuspensions development is a promising strategy to incorporate this type of drug, since it offers important advantages, such as particle size reducing of drug, which may lead to the increase of the dissolution and permeability rates of the drug. Additionaly, responsive-polymers can undergo in situ sol-gel phase transition, promoting mucoadhesion process followed by a greater retention of system in the action site. In this sense, the aim of this work was to develop micro and nanosuspensions associated to mucoadhesive polymers for colon specific release of MTX. The particles were obtained from Bottom-up method by acid-base reactions, employing the Ultra- Turrax or Sonicator and hydroxypropylmethylcellulose (HPMC) and poloxamer 407 (P407) as stabilizing. Polyacrylic acid (PAA), poloxamer 407 and gellan gum, which have different mucoadhesion mechanisms (pH, temperature and ionic concentration) were incorporated. The physic-chemical characterization of micro/nanosuspensions was realized by light scattering, measurement of zeta potential, scanning electron microscopy (SEM), texture profile analysis (TPA) and ex vivo mucoadhesion test. In the bottom-up method, the conditions were optimized to reach the solubilization and, mainly, the precipitation of drug. This variation in precipitation conditions showed that increasing the acid proportion is possible to modulate the particle size to the micro/nano-range, in the absence of stabilizer. The nanosuspensions exhibited pH above 5.0, while the microsuspensions below 4.0. For microsuspensions, analysis of the results showed that depending on the stirring process and type of stabilizer used it was possible ...